Genetic diagnosis of familial hypercholesterolaemia by targeted next‐generation sequencing. (21st May 2014) - Maglio, C.; Mancina, R. M.; Motta, B. M.; Stef, M.; Pirazzi, C.; Palacios, L.; Askaryar, N.; Borén, J.; Wiklund, O.; Romeo, S.
Abstract: Objectives: The aim of this study was to combine clinical criteria and next‐generation sequencing (pyrosequencing) to establish a diagnosis of familial hypercholesterolaemia (FH). Design, setting and subjects: A total of 77 subjects with a Dutch Lipid Clinic Network score of ≥3 (possible, probable or definite FH clinical diagnosis) were recruited from the Lipid Clinic at Sahlgrenska Hospital, Gothenburg, Sweden. Next‐generation sequencing was performed in all subjects using SEQPRO LIPO RS, a kit that detects mutations in the low‐density lipoprotein receptor ( LDLR), apolipoprotein B ( APOB ), proprotein convertase subtilisin/kexin type 9 ( PCSK9 ) and LDLR adapter protein 1 ( LDLRAP1) genes; copy‐number variations in the LDLR gene were also examined. Results: A total of 26 mutations were detected in 50 subjects (65% success rate). Amongst these, 23 mutations were in the LDLR gene, two in the APOB gene and one in the PCSK9 gene. Four mutations with unknown pathogenicity were detected in LDLR . Of these, three mutations (Gly505Asp, Ile585Thr and Gln660Arg) have been previously reported in subjects with FH, but their pathogenicity has not been proved. The fourth, a mutation in LDLR affecting a splicing site (exon 6–intron 6) has not previously been reported; it was found to segregate with high cholesterol levels in the family of the proband. Conclusions: Using a combination of clinical criteria and targeted next‐generation sequencing, we have achieved FH diagnosis with a high success rate. Furthermore, we identified a new splicing‐site mutation in the LDLR gene.